Use of medical marijuana in cystic fibrosis patients - Michael J. Stephen; Jared Chowdhury; Luis Arzeno Tejada; Robert Zanni; Denis Hadjiliadis (BMC, 2020)
Abstract Background The usage and attitudes towards medical marijuana in Cystic Fibrosis (CF) patients is unknown. Through the use of a survey we aim to clarify rates and reasons for use. Methods An anonymous survey was sent out to six centers in the Mid-Atlantic region of the United States. Use of and reason for medical marijuana was assessed, along with attitudes of the perceived utility of medical marijuana. Results A total of 637 surveys were sent out, and 193 surveys were returned (30.3% return rate). Three did not give consent, and one was empty, for a total of 189 completed surveys. 31 subjects (16.5%) reported having used marijuana for medical purposes in their lifetime, with 29 (15.4%) of these in the past year. The most used forms were edible and vaporized. The most common indications for usage were pain and stress. 28 out of 31 found marijuana to be a great deal effective for their symptoms. 21 of the 31 rated marijuana very important or important to their health. There were two reported side effects, both mild. Of 156 subjects who responded to the question if they would be interested in medical marijuana if available, 72 (46.2%) replied yes. Conclusion The use of marijuana for medical reasons was 15.4% in the past year in this sample CF population, although more expressed interest if it was available through prescription. Side effects were rare. CF physicians are going to have to familiarize themselves with advantages and disadvantages of medical marijuana as there is a great deal of interest within the community, and legalization becomes more common.